Signalling mechanisms involved in TNF-α mediated cytoprotection during ischaemic injury in a C2C12 muscle cell line - Loos, Benjamin (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2006.